Dibenarkan oleh Iman, Bukan Perbuatan: Refleksi Pembenaran Menurut Roma 3:21-31 - Tambun, Roy Haries Ifraldo (KHARISMATA: Jurnal Teologi Pantekosta, 2025)
In theological studies of Christianity, the doctrine of justification is a fundamental topic that requires comprehensive discussion. Thoroughly, Romans 3:21-31 explains that justification originates from the righteousness of God, not from human works. In the contemporary era, issues regarding truth claims have become increasingly prevalent, leading to attitudes of superiority between individuals. Therefore, this study aims to analyze Romans 3:21-31 to explain that human justification is derived from the righteousness of God, not from human deeds, thus eliminating any basis for humans to elevate their own sense of superiority. The method used in this research is biblical exegesis, involving an in-depth analysis of both the textual and historical contexts of Romans 3:21-31. The study’s findings show that justification is an act of God who justifies humans through faith in Jesus Christ, not through works of the law. Faith is understood as both an existential response and a gift from God that enables humans to receive justification. In conclusion, salvation is solely the initiative and work of God, received with humility through faith as His gift.     Dalam kajian teologis kekristenan, doktrin pembenaran menjadi sebuah bagian yang fundamental untuk dibahas secara komprehensif. Secara komprehensif, Roma 3:21-31  menjelaskan pembenaran bersumber dari kebenaran Allah bukan perbuatan manusia. Dalam era kontemporer isu truth claim semakin banyak terjadi yang menimbulkan paham superior antara dirinya dengan orang lain. Oleh karena itu, Penelitian ini bertujuan untuk menganalisis Roma 3:21-31 untuk menjelaskan bahwa pembenaran manusia bersumber dari kebenaran Allah, bukan dari perbuatan manusia sehingga tidak ada alasan untuk manusia dapat meninggikan superioritas dirinya. Metode yang digunakan dalam penelitian ini adalah tafsir Biblis dengan menganalisis konteks teks maupun konteks historis Roma 3:21-31. Hasil penelitian menunjukkan bahwa pembenaran adalah tindakan Allah yang membenarkan manusia melalui iman dalam Yesus Kristus, bukan melalui perbuatan hukum Taurat. Iman dipahami sebagai respons eksistensial dan anugerah Allah, yang memampukan manusia untuk menerima pembenaran. Kesimpulannya, keselamatan adalah inisiatif dan karya Allah semata, yang diterima dengan kerendahan hati melalui iman sebagai anugerah-Nya.